2023
DOI: 10.1093/jmt/thad015
|View full text |Cite
|
Sign up to set email alerts
|

Music Therapy Increases Social and Emotional Well-Being in Persons With Dementia: A Randomized Clinical Crossover Trial Comparing Singing to Verbal Discussion

Abstract: The number of people living with Alzheimer’s disease and related dementias (ADRD) is growing proportional to our aging population. Although music-based interventions may offer meaningful support to these individuals, most music therapy research lacks well-matched comparison conditions and specific intervention focus, which limits evaluation of intervention effectiveness and possible mechanisms. Here, we report a randomized clinical crossover trial in which we examined the impact of a singing-based music therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
3
7
0
Order By: Relevance
“…Person-centred playlists not only enabled the reminiscence of family, places, love, and loss, but also became a means of encouragement for the residents to participate in physically and cognitively stimulating activities. We found, similar to other studies, an improvement in initiation and response of the RwADs, while the duration of the effectiveness varied among the studies [27,28,47]. While the effect of music is comparable with a low to medium effect size [46], the person-centred playlist based on each resident's preferences and cultural background and the residents' engagement by the musicians to the familiar songs and activities contributed to their connection to memory, reduced agitation, and functional improvements.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Person-centred playlists not only enabled the reminiscence of family, places, love, and loss, but also became a means of encouragement for the residents to participate in physically and cognitively stimulating activities. We found, similar to other studies, an improvement in initiation and response of the RwADs, while the duration of the effectiveness varied among the studies [27,28,47]. While the effect of music is comparable with a low to medium effect size [46], the person-centred playlist based on each resident's preferences and cultural background and the residents' engagement by the musicians to the familiar songs and activities contributed to their connection to memory, reduced agitation, and functional improvements.…”
Section: Discussionsupporting
confidence: 86%
“…This study was about the effectiveness of person-centred music sessions and culturally appropriate group sessions in improving psychological wellbeing of RwADs of rural aged care homes in Australia. Music-based interventions were identified as a tool for improving person-centred care plans in rural aged care homes, in the Harmony in the Bush study, for RwADs who showed moderate to severe pain, aggression, agitation, anxiety, and depression as identified in the recent quantitative and qualitative studies [27][28][29]38,39]. The integration of person-centred music into care plans presented a high cognitive and executive functional capacity among the residents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations